Respuesta :
Answer:
Given the equation: 4(2x-1)+5 = 3+2(x+1) .....[1]
Distributive property states that when a number is multiplied by the sum of two numbers, then the first number can be distributed to both of those numbers and multiplied by each of them separately.
i.e, [tex]a\cdot (b+c) = a\cdot b+ a\cdot c[/tex]
Applying distributive property, in [1]we get;
[tex]4 \cdot(2x) -4 \cdot 1 + 5 = 3 +2 \cdot x + 2\cdot 1[/tex]
Simplify:
[tex]8x -4 + 5 = 3 + 2x + 2[/tex] .....[2]
Like terms are those terms that have the same variables and powers
Combine like terms on each side in equation [2];
8x +(-4+5) = (3+2) +2x
Simplify:
8x + 1 =5 + 2x
The terms which Carey combine are; -4 +5 and 3 + 2
Answer:
-4+5 and 3+2
Step-by-step explanation:
it has to have the and btw :)